2018
DOI: 10.1021/acs.inorgchem.8b01692
|View full text |Cite
|
Sign up to set email alerts
|

Intracation and Interanion–Cation Charge-Transfer Properties of Tetrathiafulvalene-Bismuth-Halide Hybrids

Abstract: Tetrathiafulvalene (TTF) derivatives as promising hole transport materials in assembling hybrid halide perovskite solar cells have attracted great attention; however, electron transfer or charge-transfer (CT) between TTF and metal halides has been studied with less detail at the molecular level. Using molecular models, we herein report four new TTF-bismuth-halides assembled by methylated or protonated bis(4'-pyridyl)-tetrathiafulvalene cations, (MePy)TTF or (HPy)TTF, and bismuth-halide anions. Single crystal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…At the same time, the majority of these compounds have rather wide band gaps exceeding 2 eV, which makes them poor light harvesters. However, recent literature provides several examples of hybrid iodobismuthates with low band gaps, ranging from 1.59 to 1.80 eV [ 32 , 33 , 34 , 35 , 36 ]. These compounds contain various organic cations and, more importantly, have different dimensionality of the anionic substructure, ranging from isolated anions to vertex-sharing BiI 5 chains to edge-sharing BiI 4 – chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the majority of these compounds have rather wide band gaps exceeding 2 eV, which makes them poor light harvesters. However, recent literature provides several examples of hybrid iodobismuthates with low band gaps, ranging from 1.59 to 1.80 eV [ 32 , 33 , 34 , 35 , 36 ]. These compounds contain various organic cations and, more importantly, have different dimensionality of the anionic substructure, ranging from isolated anions to vertex-sharing BiI 5 chains to edge-sharing BiI 4 – chains.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, they are multifold weak interactions that include hydrogen bonds (mainly (N)H•••I) as well as interanionic I•••I interactions [36][37][38][39][40][41][42]. DFT calculations reveal that weak non-covalent bonds are capable of promoting charge mobility along the direction of spreading such bonds in the crystal structure [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Such templating may give rise to properties from the cooperative behavior (e.g., electrical transport) not found in simple packings of the molecules, 16 and spatial charge separation within the bulk of the material (e.g., (Pb2I6)•(H2DPNDI)•(H2O)•(NMP)). 17 A great diversity of compounds appears in the tetrathiofulvalene (TTF) based charge-transfer salts (e.g., TTF3SnCl6, (TTF)BiI4, (TTF)Pb2I5), [18][19][20][21] in which the inorganic rarely shows spatial connectivity. A recent study has shown that the connectivity of the inorganic subunit can be modified in the compounds (TMP) that structural modification can be achieved, although the organic cation is not optoelectronically active.…”
Section: Introductionmentioning
confidence: 99%
“…Equilibrium speciation of bismuth­(III) at different pHs was calculated by Visual MINTEQ 3.1 using experimental ion concentrations as initial parameters. The optimized molecular geometries and energies of the system were obtained by density functional theory (DFT) calculations using Gaussian 09, where H, C, N, and O atoms were performed using the B3LYP/6–311G­(d,p) basis set, and Bi and I atoms using the LanL2DZ basis set . Additional basis set superposition error (BSSE) corrections were carried out for the interactions between amino acids (fragment A) and high-Z element ions (fragment B), and the changes in the system energy during noncovalent binding are given by eq : …”
Section: Experimental Sectionmentioning
confidence: 99%